Pengaruh Pengelolaan Wakaf Tanah Produktif Terhadap Peningkatan Kesejahteraan Masyarakat di Kecamatan Siman, Ponorogo. - Abdul Latif; Rofiqy Nurus Sanusi (Universitas Darussalam Gontor, 2022)
According to Indonesian Law no. 11 of 2009 concerning welfare, social welfare is a condition for the fulfillment of the material, spiritual and social needs of these citizens in order to live properly and develop themselves so that they can carry out social functions. The birth of the Law of the Republic of Indonesia No. 41 of 2004 concerning Waqf which leads to empowerment of waqf, is one of the instruments in building the socio-economic life of the community. According to data released by the Indonesian Waqf Board (BWI), the number of donated land locations in Siman District is 147 places, with a land area of 12.70 hectares, covering 5.22 hectares that have been certified as waqf land and 7.47 hectares are not yet certified land. The number of donated land in Siman Subdistrict that has not been certified is more than that which has been certified. Siman subdistrict, Ponorogo was chosen as the place for research because of the large number of waqf lands and boarding schools whose management was not optimal in several places and this had an effect on the welfare of the community. This study aims to determine how much the potential and impact of the Management of Productive Land Waqf in Siman District on Community Welfare. The method used in this research is quantitative methods and data collection techniques using primary data (documentation and questionnaires) and secondary data (official documents of the Siman District Office of Religious Affairs, data from the official website of the Indonesian Waqf Board and from the Central Statistics Agency). The sampling technique was simple random sampling and data collection used a questionnaire method with a Likert scale. Data analysis used simple linear regression and data processing used SPSS 21 software. The results of this study indicate that the management of productive land waqf has a relationship with the welfare of the community. The results of this study indicate that the greater the potential of Productive Land Waqf Management, the greater the impact on Community Welfare. For now, the welfare of the community has only been affected by 18.1% by the management of the productive land waqf, while the sisanaya is influenced by other variables not examined in this study. Researchers suggest that the management of productive land waqf can be maximized.